Supplementing a blend of magnesium oxide to feedlot cattle: effects on ruminal, physiological, and productive responses - Colombo, Eduardo A.; Cooke, Reinaldo F.; Araújo, Ana Clara R [UNESP]; Harvey, Kelsey M.; Pohler, Ky G.; Brandão, Alice P. (Oxford University Press (OUP), 2022)
This experiment evaluated ruminal, physiological, and productive responses of feedlot cattle consuming a corn-based finishing diet that included different levels of a magnesium oxide (MG) blend. Yearling cattle (58 heifers and 62 steers) were ranked by sex and initial body weight (BW; 407 ± 3.1 kg), and allocated to 4 groups of 30 animals each. Groups were housed in one of four drylot pens (30 × 12 m) equipped with GrowSafe automated feeding systems (Model 6000E, 4 bunks/pen) during the experiment (days -14 to 117). On day 0, groups were randomly assigned to receive a total-mixed ration without (CON; n = 30) or with the inclusion (as-fed basis) of MG at 0.25% (MG25; n = 30), 0.50% (MG50; n = 30), or 0.75% (MG75; n = 30) until slaughter on day 118. Individual feed intake was recorded daily, and BW was recorded every 14 d and prior to slaughter (day 117). Blood samples were collected on days 0, 28, 56, 84, and 112, and hair samples were collected on days 0, 56, and 112 from the tail-switch. On day 42, eight rumen-cannulated steers (BW = 492 ± 8.0 kg) were housed with yearling cattle (1 pair/pen). Pairs rotated among groups every 14 d, resulting in a replicated 4 × 4 Latin square design (n = 8/treatment; days 42 to 98). Rumen pH was measured on days 7 and 14 of each period (0800, 1200, 1600, and 2000 h). Orthogonal contrasts were used to determine if inclusion of MG (0%, 0.25%, 0.50%, or 0.75% of the diet) yielded linear or quadratic effects, and to explore overall effect of MG supplementation (CON vs. MG25 + MG50 + MG75). No treatment differences were noted (P ≥ 0.31) for BW gain, feed intake, or feed efficiency. Cattle supplemented with MG tended to have less carcass marbling (P = 0.07) compared with CON. Inclusion of MG linearly increased (P < 0.01) mean plasma concentrations of magnesium and tended to linearly decrease (P = 0.09) mean plasma concentrations of haptoglobin. Cattle supplemented with MG had greater (P < 0.01) mean plasma concentrations of cortisol compared with CON. Hair cortisol concentration did not differ between treatments on day 56 (P ≥ 0.25) and linearly decreased (P < 0.01) with MG inclusion on day 112 (treatment × day; P = 0.02). Inclusion of MG linearly increased (P = 0.03) mean rumen pH, but these outcomes were mostly noted during the last two sampling of the day (treatment × hour; P = 0.02). Collectively, supplemental MG was effective in controlling rumen pH in cattle receiving a corn-based finishing diet, but without improvements in feedlot performance and carcass merit.

Acidosis is a common digestive disorder in feedlot cattle consuming high-grain diets, resulting in excessive accumulation of organic acids and pH reduction in the rumen. Sub-acute acidosis is the most prevalent form of acidosis in feedlot cattle, and it is difficult to diagnose due to limited clinical signs, but directly impairs cattle health and productivity. This study evaluated the inclusion of a blend of magnesium oxide (MG) into feedlot diets, a novel neutralizing agent to control rumen pH and mitigate sub-acute acidosis. More specifically, cattle received a corn-based diet with the inclusion of MG at different levels (0%, 0.25%, 0.50%, or 0.75% of the diet). Ruminal pH increased as dietary MG inclusion increased, particularly as cattle consumed feed toward the end of the day. Concentrations of plasma haptoglobin and cortisol in the tail-switch hair decreased as dietary MG inclusion increased, indicating that MG supplementation reduced inflammatory and chronic stress resultant from sub-acute acidosis. However, no benefits from MG were noted for cattle productive traits, including growth rate, feed efficiency, and carcass merit traits. Therefore, supplemental MG appears to be effective in controlling rumen pH in cattle receiving a corn-based finishing diet, but without improvements in feedlot performance and carcass quality.
Keywords: acidosis; feedlot cattle; magnesium oxide; physiology; rumen